Managing multiple myeloma in the over 70s: A review. Issue 2 (February 2015) - King, Andrew J; Gooding, Sarah; Ramasamy, Karthik
Highlights: The management of myeloma in the over 70s differs from younger patients: treatment goals vary and underlying co-morbidities have to be taken into account. Age alone should not be a barrier to intensive treatment. Comprehensive geriatric assessment is indicated in the over 70s. Abstract: Multiple myeloma (MM) remains an incurable malignancy. Approximately 37% of patients with plasma cell myeloma are over the age of 75 and the median age of diagnosis is 70. The management approach to over 70s differs from younger patients, as treatment goals may vary and underlying co-morbidities and expected treatment related toxicities have to be taken into account. Individualisation of management is important, aiming to achieve the best response whilst minimising adverse events. A proportion of patients will be unable to tolerate any treatment with palliation being appropriate. Age alone should not be a barrier to treatment however, with some fit patients over the age of 70 potentially benefitting from intensive treatment options including high dose chemotherapy with autologous stem cell rescue. Comprehensive geriatric assessment is indicated in the over 70s; this should be employable in a clinic outpatient setting to make it feasible. Outcomes of this assessment potentially help physicians' choice of therapy. For decades the combination of Melphalan and prednisolone was the standard of care for older MM patients. Over the last ten years, newer drugs and combinations have improved therapeutic options for patients but are yet to demonstrate vast improvement in overall survival in this cohort.